Play-based Andragogy through 3D Jigsaw Puzzle: Enhancing Social Engagement and Collaborative Descriptive Writing - Rahmadila Eka Putri (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2025)
Play-based approach, traditionally associated with childhood education, has shown significant potential in higher education by fostering cognitive and social engagement among emerging adults. This study examined the effectiveness of a play-based approach using 3D jigsaw puzzles in enhancing social engagement and descriptive writing skills among first-semester students in the English for Business and Professional Communication program at State Polytechnic of Sriwijaya. Using a quasi-experimental design with total sampling (n = 43), students were divided into an experimental group (n = 23) and a control group (n = 20). A mixed-method approach, combining pre- and post-tests, rubric-based analysis, closed-ended questionnaire, and non-participative observation, ensured comprehensive evaluation and triangulation of findings. Results revealed that the experimental group demonstrated more positive perceptions and greater improvement in descriptive writing (+13 points, 18.31%) compared to the control group (+8 points,11.11%). Rubric analysis indicated richer details, clearer organization, and stronger sensory language, while observation highlighted higher engagement, lower stress, and improved collaboration. The study concludes that the play-based approach using 3D jigsaw puzzles effectively enhances social engagement and descriptive writing, reaffirming its pedagogical value as an innovative andragogical framework for fostering creativity, collaboration, and holistic development in higher education.